Relevant Factors in The Post-Merger Systems Integration and Information Technology in Brazilian Banks - Marcel Ginotti Pires (FUCAPE Business School, 2017)
This article discusses the factors present in post-merger integration of Systems and Information Technology (SIT) that lead to positive and negative results in mergers and acquisitions (M & A). The research comprised three of the largest acquiring banks in Brazil. We adopted two methods of research, qualitative, to operationalize the theoretical concepts and quantitative, to test the hypotheses. We interviewed six executives of banks that held relevant experience in M & A processes. Subsequently, we applied questionnaires to IT professionals who were involved in the SIT integration processes. The results showed that the quality and expertise of the integration teams and managing the integration were the most relevant factors in the processes, with positive results for increased efficiency and the increased capacity of SIT. Negative results were due to failures in exploiting learning opportunities, the loss of employees and the inexpressive record of integration procedures.